Expressão de genes relacionados ao turnover proteico no músculo esquelético de tourinhos Angus e Nelore - Busato, Karina Costa (2015)
In this study, we aimed at evaluating the expression of genes related to the regulation of muscle protein turnover in the Longissimus dorsi (LD) of Angus (A) and Nellore (N) bulls, in addition to estimating the within breed correlations of gene expression and performance traits. We studied 13 genes and transcription factors related to the IGF -1 and myostatin pathways. Thirteen animals from each breed, with initial average life weight of 381.2 ±11.8 kg were used in a completely randomized, 2 x 2 factorial design (two breeds and two feeding levels). The diet consisted of corn silage and a corn-soybean meal concentrate, in a roughage to concentrate ratio of 30:70. The treatments consisted of ad libitum (AL, with nine animals from each breed) or restriction feeding (R, a 55% restriction of total DMI of AL animals, calculated as the percentage of metabolic BW, with four animals of each breed). The duration of the experimental period was of 82 days, preceded by a 28-day adaptation period. The performance traits evaluated were slaughter body weight (SBW), total, initial and final average daily gain (ADGt, ADGi and ADGf, measured from beginning to end of the trial period, from the beginning of the trial to mid-trial and from mid-trial to the end of the trial, respecti vely), hot carcass weight, LD weight (LDW) and rib eye area (REA). Subsequent to the slaughter, samples were taken from the LD muscle between the 12th and 13th ribs in order to analyze gene expression by means of quantitative reverse transcription polymerase chain reaction. There was no difference (P > 0.05) in the expression of any of the studied genes between AAL and NAL. Feed restriction increased the expression of the IGF-1 receptor (IGF1R, P < 0.001), muscle ring finger 1 (MuRF1, P = 0.05) and mothers against decapentaplegic homolog 3 (Smad3, P = 0.04), while decreasing the expression of IGFBP5 (P < 0.01). The REA was negatively correlated to glycogen synthase kinase 3β (GSK3β, P = 0.01), myostatin (MSTN, P = 0.02) and MuRF1 (P = 0.05). The HCW was negatively correlated to GSK3β (P = 0.01), MSTN (P = 0.01) and tended to a negative correlation to IGFBP5 (P = 0.07), while the LDW tended to a negative correlation to GSK3β (P = 0.08). Genes MuRF1, Smad3 and IGFBP5 seem to be important for muscle growth, and may be worthy of further investigation as future strategies for increasing muscle in livestock.